Intensifying homestead climate-smart agriculture and the challenges to its wider adoption in Azuari watershed, Northwest Ethiopia - Debie, Ermias (Frontiers in Sustainable Food Systems, 2024)
Introduction The adoption of climate-smart agriculture practices (CSAPs) at the plot level is a promising yet underutilized strategy in Ethiopia, where subsistence farming predominates. This study investigates the factors influencing the intensity of CSAPs on homesteads and identifies key barriers to their broader adoption. Methods Quantitative data were collected through household surveys. Multiple Linear Regression (MLR) analysis was employed to examine the relationship between the independent variables and farmers' decisions to intensify CSAPs. Results The findings reveal that slope gradient, extension contacts, farming experience, dependency ratio-induced labor, and livestock diversity significantly impact farmers' decisions to enhance CSAPs. Major barriers include insecure land tenure, poor management of open grazing, labor-intensive practices, and limited access to agricultural inputs. Discussion To promote the widespread implementation of CSAPs, it is imperative that these variables are prioritized in agricultural extension policies. Addressing these barriers is essential for enhancing the adoption of CSAPs, which will significantly contribute to sustainable agricultural development in Ethiopia.